2022
DOI: 10.3390/land11030410
|View full text |Cite
|
Sign up to set email alerts
|

Using Land to Promote Refugee Self-Reliance in Uganda

Abstract: Around the world, the number of people displaced from their homes continues to increase due to political conflict and climate change. The Ugandan government’s policy for settling refugees shifts the focus from seeing refugees as humanitarian obligations to recognizing that refugee settlements bring improved services and infrastructure that can serve both refugees and residents of the host communities. A key aspect of this policy is to provide refugees with land use rights, so they are able to achieve “self-rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…An example of this is Uganda, where refugees are provided with a pot of land to support self-reliance. Over time size of the plots of lands given to refugees decrease as less land in the settlement areas is available [69]. Contextual limitations, such as the available amount of biomass for cooking, can also lead to distributional challenges with increasing numbers of displaced persons hosted.…”
Section: Data Insights From a Country Perspective Number Of Displaced...mentioning
confidence: 99%
“…An example of this is Uganda, where refugees are provided with a pot of land to support self-reliance. Over time size of the plots of lands given to refugees decrease as less land in the settlement areas is available [69]. Contextual limitations, such as the available amount of biomass for cooking, can also lead to distributional challenges with increasing numbers of displaced persons hosted.…”
Section: Data Insights From a Country Perspective Number Of Displaced...mentioning
confidence: 99%
“…An example of this is Uganda, where refugees are provided with a plot of land to support self-reliance. Over time, the size of the plots of land given to refugees decreases as less land in the settlement areas is available [69]. Contextual limitations, such as the available amount of biomass for cooking, can also lead to distributional challenges with increasing numbers of displaced persons hosted.…”
Section: Data Insights From a Country Perspective 431 Number Of Displ...mentioning
confidence: 99%
“…The How the World Views Migration Report (2015) of the International Organization for Migration (IOM) shows that majority of the survey respondents in major world regions (with a few exceptions in Europe) supported immigration to either remain the same or increase [9]. In addition, in terms of humanitarian planning, due to increasing instances of protracted displacements, local integration and self-settlement in urban areas have been considered complex but a future solution [5,[10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, campscapes provide urban citizenship to outcasts and outsiders and influence the local socio-economic, political, physical, and legal conditions of a city [37]. Research in African countries has shown that local integration and self-settlement in urban areas are viable solutions, as refugees gain economic self-sufficiency [38,39] and bring urban services that serve both refugees and host communities [12]. Thus, despite varied research on shifting urban dynamics due to migrant integration, little attention has been given to understanding its influence on urban frameworks and vice versa [40].…”
Section: Introductionmentioning
confidence: 99%